The Effectiveness of Two-Stage Adsorption Using Adsorbents Activated with Strong Acid and Base Solutions on Biogas - Tira, Hendry Sakke; Padang, Yesung Allo; Arifin, Muh Samsul (Universitas Medan Area, 2024)
This study discusses the development of a two-stage adsorption application to enhance methane content in biogas. The adsorption process utilizes zeolite sourced from Lombok Island. To achieve this objective, the zeolite is activated using HCl and KOH solutions, each with concentrations of 3 Molar and 20%, respectively. Additionally, the zeolite is physically activated by heating it in a furnace at 300°C for 3 hours, followed by chemical activation. Research findings indicate that activation of zeolite with these compounds yields a significant increase in methane content compared to adsorption using non-activated zeolite. The improvement in methane content reaches at least 45%. These results demonstrate substantial potential in enhancing biogas production efficiency through two-stage adsorption using chemically activated zeolite. Additionally, this outcome underscores the understanding that without activation, zeolite from Lombok cannot function optimally as an adsorbent.